PENDAMPINGAN DAN PELATIHAN PENENTUAN HARGA POKOK PRODUKSI PADA UMKM BATIK PUTRI SANGGABUANA KARAWANG - Rohma Septiawati ,; Fista Apriani Sujaya ,; Dhea Imroatul Fatihah,; Septiana Rahayu ,; Moch Agus Ariffianto, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have become the backbone of Indonesia's economy, playing an increasingly significant role in creating jobs without requiring specific qualifications. In this context, the batik industry, with its rich artistic and cultural value, stands out as a potential sector for local economic growth. However, MSMEs in this industry, including Batik Putri Sanggabuana in Karawang, often face challenges in determining the cost of goods manufactured (COGM). A lack of understanding and skills in production cost calculation methods can result in suboptimal pricing decisions, which may even threaten business sustainability. Therefore, focused assistance and training are essential to help Batik Putri Sanggabuana accurately and competitively determine COGM, thereby enhancing profitability and operational sustainability.